Działalność opiekuńcza jako czynnik wychowawczy na ziemiach polskich pod zaborami - Partyka, Wiesław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Caring for others stems from the natural law and is one of the fundamental social functions. For centuries, the Church has been engaged in providing care rooted in the evangelical commandment to love your neighbor as yourself. Over time, lay people influenced by the Enlightenment ideals got increasingly involved in it. During the Partitions, health care organizations not only cared for people in need, but also had a much broader mission. Caring activities significantly shaped upbringing and built a moral value-based sense of community and responsibility for others to create social solidarity and bring up the young as people sensitive to others’ needs.